Changes in Stroke Patient's Awareness through the Driving Simulation in Rainy Weather. (3rd July 2021) - Choji, Yuki; Yoshino, Ryota; Yoshimura, Yuko
Abstract: Objectives: This study was conducted to examine the situation awareness of stroke patients by means of the simulation and practice for driving in rain (SPDR). Methods: Twenty-one stroke patients underwent the SPDR. Then, semi-structured interviews were conducted before and after the SPDR. The data of the interviews were analyzed through qualitative analysis based on content analysis. Results: As a result of the qualitative analysis, it was found that many patients became aware of driving risks, of which they had not previously been aware, through the simulation; these were categorized as improved awareness and confusion. Conclusions: The findings from the qualitative approach indicate that the SPDR is a useful strategy for stroke patients to improve the awareness of driving risks.